Understanding the function of conserved variations in the catalytic loops of fungal glycoside hydrolase family 12. Issue 8 (27th February 2014) - Damásio, André R.L.; Rubio, Marcelo V.; Oliveira, Leandro C.; Segato, Fernando; Dias, Bruno A.; Citadini, Ana P.; Paixão, Douglas A.; Squina, Fabio M.
ABSTRACT Enzymes that cleave the xyloglucan backbone at unbranched glucose residues have been identified in GH families 5, 7, 12, 16, 44, and 74. Fungi produce enzymes that populate 20 of 22 families that are considered critical for plant biomass deconstruction. We searched for GH12‐encoding genes in 27 Eurotiomycetes genomes. After analyzing 50 GH12‐related sequences, the conserved variations of the amino acid sequences were examined. Compared to the endoglucanases, the endo‐xyloglucanase‐associated YSG deletion at the negative subsites of the catalytic cleft with a SST insertion at the reducing end of the substrate‐binding crevice is highly conserved. In addition, a highly conserved alanine residue was identified in all xyloglucan‐specific enzymes, and this residue is substituted by arginine in more promiscuous glucanases. To understand the basis for the xyloglucan specificity displayed by certain GH12 enzymes, two fungal GH12 endoglucanases were chosen for mutagenesis and functional studies: an endo‐xyloglucanase from Aspergillus clavatus (AclaXegA) and an endoglucanase from A. terreus (AtEglD). Comprehensive molecular docking studies and biochemical analyses were performed, revealing that mutations at the entrance of the catalytic cleft in AtEglD result in a wider binding cleft and the alteration of the substrate‐cleavage pattern, implying that a trio of residues coordinates the interactions and binding to linear glycans. The loop insertion at the crevice‐reducing end of AclaXegA is critical for catalytic efficiency to hydrolyze xyloglucan. The understanding of the structural elements governing endo‐xyloglucanase activity on linear and branched glucans will facilitate future enzyme modifications with potential applications in industrial biotechnology. Biotechnol. Bioeng. 2014;111: 1494–1505. © 2014 Wiley Periodicals, Inc.